Comprehensive performance evaluation of satellite-based and reanalysis rainfall estimate products in Ethiopia: For drought, flood, and water resources applications. - Desta Yoseph Wodebo; Assefa M Melesse; Tekalegn Ayele Woldesenbet; Kirubel Mekonnen; Ahmed Amdihun; Diriba Korecha; Hailay Zeray Tedla; Gerald Corzo; Asaminew Teshome (Journal of Hydrology: Regional Studies)
Study Region Ethiopia: This study assessed the accuracy of ten satellite-based and reanalysis rainfall estimation products across Ethiopia via direct comparisons with 430 in-situ datasets from 2001 to 2020. The performance of these rainfall products at various spatial and temporal scales was validated via five continuous and six categorical metrics to identify the most reliable products for the application of drought monitoring, flood risk analysis, and water resources management in 92 zonal administrative and 76 subbasins boundaries in Ethiopia. New hydrological insights for the region: This study revealed that the performance of rainfall products varies over space and time and is heavily impacted by the diverse climate and topography of Ethiopia. In general: ARCv2.0 and CHIRPSv2.0 detected rainfall of less than 1 mm and well-captured drought-year monthly products, making them suitable for drought monitoring. The IMERG-Fv6B and TAMSATv3.1 products were found to be reliable for detecting heavy rainfall and suggested for flood monitoring. Similarly, for water resources potential studies, CHIRPSv2.0 and MSWEPv2.8 were identified as reliable products at all 50 spatial scales of the analysis. This study offers multiple novel perspectives for selecting location-specific suitable rainfall products as decision-support information for water resources, flood risk management, and drought monitoring in Ethiopia. The findings also imply the importance of bias correction or blending of satellite data for a better representation of the true value.